2018
DOI: 10.1111/jzo.12561
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dimorphism in the sonic system and otolith morphology of Neobythites gilli (Ophidiiformes)

Abstract: Although males and females of many sound‐producing fish species may show differences at the level of the sonic apparatus, otoliths are usually species specific having intraspecific variation only if exposed to different environmental condition or in relation with the fish size. This study reports sexual dimorphism at the level of both otolith shape and sonic apparatus in the ophidiid Neobythites gilli. As it is the case in other Neobythites species, sound‐producing apparatus is better developed in males. Due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…In contrast, although otolith shape variation in Atlantic cod Gadus morhua Linneaus, 1758, was mostly influenced by differences in growth rates among populations, a small but significant shape difference was observed between males and females (Campana & Casselman, ). A recent study by Parmentier, Boistel, Bahri, Plenevaux, and Schwarnzhans () reported substantial secondary sexual dimorphism in the hearing apparatus and otolith shape of the ophidiid Neobythites gilli (Goode and Bean, 1885). Since males and females of this species demonstrated similar hearing ability, it was hypothesized that differences in habitat preference (and associated environmental variables) were responsible for the observed dimorphism (Parmentier et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, although otolith shape variation in Atlantic cod Gadus morhua Linneaus, 1758, was mostly influenced by differences in growth rates among populations, a small but significant shape difference was observed between males and females (Campana & Casselman, ). A recent study by Parmentier, Boistel, Bahri, Plenevaux, and Schwarnzhans () reported substantial secondary sexual dimorphism in the hearing apparatus and otolith shape of the ophidiid Neobythites gilli (Goode and Bean, 1885). Since males and females of this species demonstrated similar hearing ability, it was hypothesized that differences in habitat preference (and associated environmental variables) were responsible for the observed dimorphism (Parmentier et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Parmentier, Boistel, Bahri, Plenevaux, and Schwarnzhans (2018) reported substantial secondary sexual dimorphism in the hearing apparatus and otolith shape of the ophidiid Neobythites gilli (Goode and Bean, 1885). Since males and females of this species demonstrated similar hearing ability, it was hypothesized that differences in habitat preference (and associated environmental variables) were responsible for the observed dimorphism (Parmentier et al, 2018).…”
Section: Secondary Sexual Dimorphism In Otolith Shapementioning
confidence: 99%
“…In summary, despite similar morphology, there appear to be major differences in frequency generation with the subfamily: in some species the frequency spectrum is determined by individual oscillations of the swimbladder and in others by the pulse-repetition rate. Both Genypterus species share many common characters with other Ophidiiformes belonging to the group 1 proposed by Howes (Howes, 1992) such as Neobythites (Ali et al, 2016;Fine et al, 2018;Parmentier et al, 2018a), Ophidion sp. (Kéver et al, 2014b;Parmentier et al, 2010Parmentier et al, , 2006a and Lepophidium sp.…”
Section: Discussionmentioning
confidence: 85%
“…Atlantic cod, G. morhua 7,75 ; flatfish spp. 9 ; plainfin midshipman, P. notatus 8 ; Neobythites gilli 76 ), a common explanation is that the sexes likely differ with respect to their somatic growth rates and metabolic rates. Growth rates, energy storage, and metabolism have rarely been explicitly compared between the sexes in our study species, but when they have, males and females have scored similarly (e.g.…”
Section: Discussionmentioning
confidence: 99%